Public Policy Supervision in Preventing Corruption of Village Fund by Women in Klambir V Kebun Village - Nana Kartika; Rahul Ardian Fikri (Yayasan Multidimensi Kreatif, 2025)
supervising public policies, particularly in the context of preventing corruption in village funds. Village funds are a source of development financing that are vulnerable to misuse if not monitored transparently and participatively. Mothers, as part of an active community element that is close to the social dynamics of the village, have great potential to encourage accountability and openness in the management of village funds. This research uses a qualitative approach with in-depth interviews, participatory observation, and documentation studies. The results show that the involvement of women in village deliberation forums, budget socialization activities, and monitoring of physical projects contributes significantly to reducing the potential for corruption practices. Additionally, their role in building collective awareness and having the courage to voice alleged irregularities is an important asset in shaping an anti-corruption culture at the village level. However, challenges remain, such as limited access to information, budget literacy capacity, and resistance from certain individuals. Therefore, capacity building and institutional support are key to strengthening the role of women as public oversight agents at the village level.